Finite element analysis to predict the cyclic performance of GFRP-RC exterior joints with diagonal bars. (15th April 2023) - Safdar, Muhammad; Sheikh, M. Neaz; Hadi, Muhammad N.S.
Abstract: This paper presents a finite element modeling (FEM) approach to predict the cyclic response of glass fiber-reinforced polymer (GFRP) reinforced concrete (RC) exterior beam-column joints with different joint details. Four GFRP-RC exterior beam-column joints detailed with U or L-shaped anchorages at the end of the longitudinal bars of the beam, horizontal stirrups and additional diagonal bars (Z or U-shaped) at the joint region were modeled and analyzed under reversed cyclic loading. The FEM cyclic behavior in terms of load-drift ratio, cracking patterns, joint shear stress and strain evolutions were compared with the experimental behaviors. The FEM predicted load-drift ratio response, cracking patterns and dissipated energy showed good correlations with the experimental results. A parametric study was conducted to evaluate the influence of compressive strength of concrete, column axial load ratio and size of the additional diagonal bar on the performance of the GFRP-RC joints. It was found that an increase in the column axial load significantly degraded the performance in terms of strength, maximum joint shear stress and ductility of the GFRP-RC joints. Also, GFRP-RC joints with additional U-bars were able to resist higher joint shear stress and drift ratio than GFRP-RC joints with additional Z-bars, respectively. Highlights: FEM approach developed to predict the cyclic response of GFRP-RC joints. U or L anchors were modeled and analyzed under reversed cyclic loading. A parametric study was conducted to predict the performance of the GFRP-RC joints.